LAHUBMAX –Priority Based Meta Task Scheduling Algorithm in multicloud - Shanthan, J. Hubert; Arockiam, L (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing plays a obvivious role in the field of web based computing.Multicloud is an advancement of the cloud computing. Multicloud is an environment comprises of more number of cloud service providers available to cater the needs of the heterogenous users. Task scheduling is one of the major issue affects the performance of the multicloud computing systems. This paper is designed to solve task based scheduling problem for the multicloud systems. Priority is one of the key concern to the service consumers. The high prioritized tasks are given due importance and they are executed in the high speed virtual machines. This article proposes a novel priority based independent task based scheduling algorithm for the multicloud environment. Fuzzy rule is used in this algorithm , to select the user prioritized tasks with larger length. Mandomi Inference system to generate a new rule to select and execute tasks. The proposed algorithm is merely emphasized on minimizing the total completion time of the tasks. There are five different categories of user priorities illustrated in this algorithm. The proposed algorithms outperforms the existing max-min algorithm in terms of makespan and cost